Conduction Cooling and Plasmonic Heating Dramatically Increase Droplet Vitrification Volumes for Cell Cryopreservation. Issue 11 (10th April 2021) - Zhan, Li; Guo, Shuang‐Zhuang; Kangas, Joseph; Shao, Qi; Shiao, Maple; Khosla, Kanav; Low, Walter C.; McAlpine, Michael C.; Bischof, John
Abstract: Droplet vitrification has emerged as a promising ice‐free cryopreservation approach to provide a supply chain for off‐the‐shelf cell products in cell therapy and regenerative medicine applications. Translation of this approach requires the use of low concentration (i.e., low toxicity) permeable cryoprotectant agents (CPA) and high post cryopreservation viability (>90%), thereby demanding fast cooling and warming rates. Unfortunately, with traditional approaches using convective heat transfer, the droplet volumes that can be successfully vitrified and rewarmed are impractically small (i.e., 180 picoliter) for <2.5 m permeable CPA. Herein, a novel approach to achieve 90–95% viability in micro‐liter size droplets with 2 m permeable CPA, is presented. Droplets with plasmonic gold nanorods (GNRs) are printed onto a cryogenic copper substrate for improved cooling rates via conduction, while plasmonic laser heating yields >400‐fold improvement in warming rates over traditional convective approach. High viability cryopreservation is then demonstrated in a model cell line (human dermal fibroblasts) and an important regenerative medicine cell line (human umbilical cord blood stem cells). This approach opens a new paradigm for cryopreservation and rewarming of dramatically larger volume droplets at lower CPA concentration for cell therapy and other regenerative medicine applications. Abstract : A novel droplet vitrification system demonstrates high post thaw cell viability (90–95%) with reduced cryoprotectant concentration (i.e., 20%) and improved vitrification throughput (i.e., ≈1000x) using larger (1–4 μL) droplet volumes. Conductive cooling and plasmonic heating approaches are employed and characterized thoroughly to substantially improve the cooling and warming rates compared to traditional convective heat transfer approaches.